Drug-repositioning opportunities for cancer therapy: novel molecular targets for known compounds. Issue 1 (January 2016) - Würth, Roberto; Thellung, Stefano; Bajetto, Adriana; Mazzanti, Michele; Florio, Tullio; Barbieri, Federica
Highlights: De novo anticancer drug discovery is challenging and repurposing in oncology is a promising field. Drug repositioning increasingly emerges as faster, cheaper and alternative drug development. Approved, old drugs could bypass early stages of drug pipeline to be used for new indications. Integrating research knowledge improves targeting and response prediction in drug repurposing. The efficacy of non-oncological drugs targeting cancer stem cells boosts drug repositioning. Abstract : Drug repositioning is gaining increasing attention in drug discovery because it represents a smart way to exploit new molecular targets of a known drug or target promiscuity among diverse diseases, for medical uses different from the one originally considered. In this review, we focus on known non-oncological drugs with new therapeutic applications in oncology, explaining the rationale behind this approach and providing practical evidence. Moving from incompleteness of the knowledge of drug–target interactions, particularly for older molecules, we highlight opportunities for repurposing compounds as cancer therapeutics, underling the biologically and clinically relevant affinities for new targets. Ideal candidates for repositioning can contribute to the therapeutically unmet need for more-efficient anticancer agents, including drugs that selectively target cancer stem cells.